2015
DOI: 10.1371/journal.pone.0127566
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Benefits of Cochlear Implantation in Children with Auditory Neuropathy

Abstract: BackgroundAuditory neuropathy (AN) is a recently recognized hearing disorder characterized by intact outer hair cell function, disrupted auditory nerve synchronization and poor speech perception and recognition. Cochlear implants (CIs) are currently the most promising intervention for improving hearing and speech in individuals with AN. Although previous studies have shown optimistic results, there was large variability concerning benefits of CIs among individuals with AN. The data indicate that different crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The inter-participant variability can be identified in this study from the performances that were unstable along consecutive teaching sessions and that did not keep stable between two consecutive sessions, what replicates the results found in the case study of Rique et al (16) . The variability results between participants, in the present study, is similar to the ones found in studies of other centers (8) and suggest that the variability between children with ANSD and CI is recurrent in relation to the learning rhythm, to the number of repetitions and to order of acquisition of the speaker's behavior (tact and echoic).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The inter-participant variability can be identified in this study from the performances that were unstable along consecutive teaching sessions and that did not keep stable between two consecutive sessions, what replicates the results found in the case study of Rique et al (16) . The variability results between participants, in the present study, is similar to the ones found in studies of other centers (8) and suggest that the variability between children with ANSD and CI is recurrent in relation to the learning rhythm, to the number of repetitions and to order of acquisition of the speaker's behavior (tact and echoic).…”
Section: Discussionsupporting
confidence: 89%
“…Dado has used CI for five months, detected speech sounds (1 of listen) and spoke isolated words (2 of language), while Flor had more than three years of CI use, recognized words in closed set (3 of listen) and constructed short sentences (4 of language). This difference in CI time of using and in the previous hearing and language categories could predict intervention success (5,8) , supposing it is more effective for Flor than for Dado. However, the present study showed that these children with ANSD and CI learned and integrated the listener and speaker tasks, by MEI, regardless the short time of CI use and the variability presented (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Treatment of profound-to-severe hearing loss in patients with AN requires cochlear implantation (CI); however, the efficacy of CI in such cases is controversial. [20][21][22][23][24] On the other hand, AN caused by OTOF mutations is thought to be a better candidate for cochlear implantation because the electrode can stimulate the auditory nerves directly, thus bypassing impaired synapses. Several reports have demonstrated an adequate level of cochlear implant performance in patients with OTOF mutations.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies it was reported that patients had some forms of hereditary nonsyndromic autosomal dominant auditory neuropathy progressing to outer hair cell malfunction causing decline in pure-tone audiometer results. Some of the patients in these series benefitted from hearing aids or FM devices but in some a CI is the only way to communicate (10)(11)(12).…”
Section: Auditory Neuropathy/dyssynchronymentioning
confidence: 99%